Optimal location of virtual generation plants in electric power systems based on optimal power flows - Mosquera, Fabricio (2020)
The present work determines the optimal location of virtual generation plants analyzing the steady state behavior of the system, the virtual generation plant combines a wide variety of distributed energy resources and operates them as a unified system. The optimal location of virtual generation plants will be identified to improve the nodal voltage profile of the power system based on optimal flows of direct current power with economic and environmental constraints. The electrical system analysis is carried out by means of optimal direct current power flows based on mixed integer linear programming, respecting economic, the chargeability of the transmission lines, the handling of the demands, the overload level, the angular deviation and the voltage profile. A literary review of virtual generation plants is carried out, which has a series of competitive advantages such as the use of renewable technologies and high energy efficiency. It also has information for the development of the optimal direct current flow.